Achieving the Nationally Determined Contribution (NDC) in Forestry Sectors: Challenges for Indonesia - Etheldreda E.L.T Wongkar (IKAT: The Indonesian Journal of Southeast Asian Studies, 2021)
Indonesia's determination in realizing the Nationally Determined Contribution target as a follow-up to the Paris Agreement resulted in concrete steps in climate change adaptation and mitigation efforts, one of which is through social forestry. This paper aims to describe the various efforts to achieve Indonesia's targets on both conditional and unconditional, as well as the application and linkage of social forestry schemes to climate change will. This research produces two conclusions. First, those conditional and unconditional targets are related in their implementation, primarily related to the development of Indonesian legislation and capacity building in achieving Nationally Determined Contribution targets. Second, namely that after the issuance of the MoEF Decree No. 83/2016, social forestry regulations in Indonesia have begun to accommodate ecological elements, although the nature are still partial in every policy momentum and are still not in line with the scope of activities of REDD+. Several critical issues that need to be followed up are the absence of uniform and applicative carbon measurement and calculation methods for beneficiary communities and national forest carbon certification system for social forestry areas, legal challenges on the recognition of Indigenous People rights, also political-economic challenges.